2002
DOI: 10.1080/01650250143000292
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative recall in married and unacquainted dyads

Abstract: Thirty younger couples between the ages of 19 and 36 (Mˆ26.0, SDˆ3.5) and thirty older couples between the ages of 56 and 85 (Mˆ67.4, SDˆ5.3) were tested on story recall, word recall, and a referential naming task. Each individual worked with the spouse and with a stranger of the other gender so that collaborative performance could be compared between familiar and unfamiliar dyads. Although participants anticipated that higher levels of recall performance would be obtained when they worked with a familiar part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 22 publications
1
63
0
2
Order By: Relevance
“…Rönnberg (1995, 1996) demonstrated that collaborative inhibition was obtained among unacquainted pairs but was reduced among pairs of good friends. Johansson et al (2005) found a similar trend in older adult couples, although the difference in collaborative inhibition between older adult married couples and unacquainted pairs did not reach statistical significance (see also Gould, Osborn, Krein, & Mortenson, 2002, for a group-level analysis of partner familiarity in older adults).…”
mentioning
confidence: 76%
“…Rönnberg (1995, 1996) demonstrated that collaborative inhibition was obtained among unacquainted pairs but was reduced among pairs of good friends. Johansson et al (2005) found a similar trend in older adult couples, although the difference in collaborative inhibition between older adult married couples and unacquainted pairs did not reach statistical significance (see also Gould, Osborn, Krein, & Mortenson, 2002, for a group-level analysis of partner familiarity in older adults).…”
mentioning
confidence: 76%
“…Other research has compared collaborative recall in groups of acquaintances and groups of strangers, with mixed results. Anderson and Ronnberg (1995) reported less collaborative inhibition in groups of friends, while Gould, Osborn, Krein, and Mortenson (2002) reported no difference between married and unacquainted dyads. Most recently, Cuc, Ozuru, Manier, and Hirst (2006) examined the effects of group dynamics (specifically, a dominant narrator) on the collaborative recall of stories by families.…”
Section: Collaborative Recallmentioning
confidence: 94%
“…Andersson and Rönnberg (1996) found that groups of friends exhibited less collaborative inhibition than groups of strangers. In contrast, Gould, Osborn, Krein, and Mortenson (2002) found no difference in collaborative recall between married and unacquainted dyads (although they did not include a nominal comparison), and Peker and Tekcan (2009) also found similar levels of collaborative inhibition for groups of friends and strangers. Despite these inconclusive findings, Rajaram and Pereira-Pasarin (2010) suggested that collaborative inhibition might be reduced in intimate groups, perhaps due to "transactive memory" (see also Wegner, 1987;Wegner, Giuliano, & Hertel, 1985), but the effects of relationship on collaborative recall are not yet clear.…”
mentioning
confidence: 91%